Health care provider responses to initial parental reports of autism spectrum disorder symptoms: results from a nationally representative sample. Issue 1 (7th November 2016) - Barnard‐Brak, Lucy; Richman, David; Ellerbeck, Kathryn; Moreno, Rosario
Abstract : Background: Health care provider (HCP) responses to initial parental report of autism spectrum disorder (ASD) symptoms were examined in relation to latency to diagnosis and child chronological age at diagnosis. Method: Secondary data analyses were conducted for a sample of 1384 parents of children with ASD utilizing data from the National Survey of Children with Special Health Care Needs (NS‐CSHCN, 2009–2010 National Survey of Children with Special Health Care Needs, 2009) and the Centers for Disease Control and Prevention Pathways to Diagnosis and Services (CDC PDS, Survey of pathways to diagnosis and services, 2011). Results: Approximately 44% of the sample experienced predominantly delayed HCP responses, 38% experienced predominantly proactive responses, while the remaining 18% experienced a relatively even mix of delayed and proactive responses across HCPs. With regard to outcomes correlated with the type of HCP response, individuals exposed to proactive HCPs were diagnosed with ASD almost a year earlier for child chronological age than individuals exposed to mixed HCPs. This difference increased beyond a year between individuals receiving proactive HCPs versus individuals experiencing delayed HCPs. Finally, after controlling for socioeconomic status, parent‐reported severity of ASD symptoms, and age at time of referral, proactive HCP was correlated with decreased time to diagnosis from parental first report of ASD symptoms. Conclusions: Results are discussed with regard to increasing proactive HCP responses to parental first concerns of ASD symptomology versus a mix or delayed responses.